IDENTIFICATION OF PROBLEMATIC BEHAVIORS AMONG LEARNERS IN CLASSROOMS BY TEACHERS IN PRIMARY SCHOOLS SOUTH AFRICA - Jacob, Lizanne; Aloka, Peter JO (International Journal of Humanity Studies (IJHS), 2023)
The study explored the identification of problematic behaviors of learners in the classroom by teachers in Midrand in the Gauteng province of South Africa. This study was informed by Bandura’s Social Cognitive theory. The multiple case study design was chosen for this study. The participants comprised fifteen teachers (15) who teach grade four in the three public primary schools in Midrand. This study employed semi-structured interviews for data collection. Thematic analysis was adopted to analyze the qualitative data.  The results of the study indicated that teachers identified the problem behaviors by observing learners in and out of class, observing disruptive behaviors, observing uncooperative learners, observing disobedience behaviors, and assessing learning difficulties. The study recommends that Life orientation teachers should teach learners to be aware of the practical skills that are required in times of crisis, when they are experiencing emotional stress, instead of acting out by displaying problem behavior.